QUALITY MANAGEMENT OF PRABULINGGIH WRITTEN BATIK SME IN ISLAMIC PERSPECTIVE OF BULUJARAN LOR VILLAGE, TEGALSIWALAN, PROBOLINGGO - Rohima; Imanuddin Abil Fida; Abdelmajid Idris Mohammed Khalil (International Journal of Multidisciplinary Reseach, 2025)
Quality is an effort that is carried out seriously with the aim of achieving a value that can provide maximum satisfaction to the user. A product is considered to have quality if the product meets the expectations of various parties, especially producers and consumers. One thing that is a common thread in the quality concept is satisfaction.  This research was carried out because the researcher wanted to know whether the Prabulinggih written batik UKM had implemented quality management in its business or not. At this research site, quality management has been implemented in its production, Prabulinggih handwritten batik is unique, how can the Prabulinggih Handwritten Batik UKM receive a positive response and appreciation from the Head of the Cooperatives and Small and Medium Enterprises Department of Probolinggo Regency. In fact, if you look at the production location, it is not very strategic, namely it is located in Janten Hamlet, Bulujaran Lor Village, Tegalsiwalan District, Probolinggo. This is what attracted researchers to conduct research on Production Quality Management in Probolinggo Written Batik UKM, Bulujaran Lor Village, Tegalsiwalan District, Probolinggo.